Corruption and Education: Empirical Evidence - Dridi, Mohamed (International Journal of Economics and Financial Issues, 2014)
Corruption is widely believed to be detrimental to economic performance. However, little empirical evidence has been presented to assess its consequences on education. Using various education indicators, this paper aims to examine the effects of corruption on education both from a quantitative and qualitative point of view. The cross-country regression analysis shows a strong link between corruption and secondary school enrollment rates, but the relationship between corruption and education quality as measured by repeater rates is weaker. The results suggest that high and rising corruption decreases significantly access to schooling. A unit increase in corruption reduces enrollment rates by almost 10 percentage points. These findings are robust to the use of alternative measure of corruption and other sensitivity analysis. Keywords: Corruption; education JEL Classifications: D73; I20